Asymmetric trehalose analogues to probe disaccharide processing pathways in mycobacteria. Issue 18 (30th April 2020) - Parker, Hadyn L.; Tomás, Ruben M. F.; Furze, Christopher M.; Guy, Collette S.; Fullam, Elizabeth
Abstract : Chemoenzymatic synthesis of azido-functionalised asymmetric trehalose analogues that are resistant to enzymatic degradation to probe carbohydrate processing pathways in mycobacteria. Abstract : The uptake and metabolism of the disaccharide trehalose by Mycobacterium tuberculosis is essential for the virulence of this pathogen. Here we describe the chemoenzymatic synthesis of new azido-functionalised asymmetric trehalose probes that resist degradation by mycobacterial enzymes and are used to probe trehalose processing pathways in mycobacteria.